Federacja Rosyjska w narodowych strategiach bezpieczeństwa Armenii, Azerbejdżanu i Gruzji .......... 59 - Gomółka, Krystyna (Rewolucja rosyjska. Spuścizna : międzynarodowe echa rewolucji, 2017)
THE RUSSIAN FEDERATION IN THE NATIONAL SECURITY STRATEGIES OF ARMENIA, AZERBAIJAN AND GEORGIA In the second decade after regaining independence, Georgia, Armenia and Azerbaijan announced their national security strategies. The documents of these countries indicated security threats such as the fear for their sovereignty and state independence, ethnic conflicts, the development of contraband and organized crime, economic dependence and deterioration of the natural environment. The foreign policy pursued by these countries and the actions undertaken were aimed at ensuring their security. The aim of the article is to show Russia’s place in the security system of Armenia, Azerbaijan and Georgia. The Russian Federation is for Armenia the guarantee of the security of its borders and its strategic partner. In Georgia’s first national security strategy, there was no explicitly stated threat from Russia. It was only in the text of the second strategy, adopted after the war in 2008, that fears against Russian aggression were clearly outlined. Georgia was seeking allies in close relations with the US. In the national security strategy of Azerbaijan, little attention has been given to Russia. Regarding the border countries, the document declares the maintenance of a peaceful neighborhood. Azerbaijan insists that the South Caucasus region be free from atomic weapons, opposes the illegal transport of weapons and military equipment to that region and advocates the demilitarization of the Caspian Sea Region.